COORDINATION OF PRIORITIES AND TASKS OF STRATEGIC DEVELOPMENT OF THE ENTERPRISE ON THE BASIS OF INDUSTRY 5.0 AND MANAGEMENT 5.0 - KUDLAENKO, Sergey; ROMANENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research updates issues of strategic planning, determination of prospects, priorities, tasks, as well as means of achieving them in the part of the planned long-term progress of the business entity. It was established that it is possible to implement such plans on the basis of the most progressive modern trends, which are breakthrough innovative technologies, as well as maximum automation of technological processes. However, such changes require adequate adaptation of business management systems and business processes to them. Therefore, the purpose of the research is to justify the priorities and tasks of strategic development of the enterprise on the basis of Industry 5.0 and Management 5.0. The possibilities of harmonizing both strategic vectors - the tasks of developing the corporate structure - are characterized. The tools and means of strategic development of the enterprise on the basis of Industry 5.0 and Management 5.0 are defined. It has been proven that the development of enterprises on the basis of Industry 5.0 provides subjects with a number of strategic advantages, such as high speed and rhythm of production, uninterrupted production and a low level of waste and losses, lower consumption intensity of production, significantly higher financial and economic efficiency of production and economic processes, ease of management, etc. However, such a vector of development requires adaptation of its management system, in other words, a transition to the construction of both the general system and partial management links on the basis of Management 5.0. It was established that such a process involves the implementation of three consecutive stages: (1) changes in the business management system, when the nature of such changes is clearly oriented towards the adaptation of the organizational and management structure to the transition to an automated type of production, increasing the role and significance of innovation management and their financial and investment provision, digitization of the business management system, relevant connections and communications; (2) intensification of the innovative activity of the enterprise, its innovative and technological development and a more active role in the relevant processes of intellectual property objects and patent-licensing activities in general; (3) increasing the volume of business and income and profit, improving the financial and economic condition, capitalization, increasing economic efficiency and using all groups of resource provision. It was concluded that the further development of both Industry 5.0 and Management 5.0 is closely correlated with the coordination of the strategic development priorities of the enterprise and the tasks of these two global trends among themselves.